2019
DOI: 10.1096/fj.201802453r
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting an old antibiotic: bacitracin neutralizes binary bacterial toxins and protects cells from intoxication

Abstract: The antibiotic bacitracin (Bac) inhibits cell wall synthesis of gram‐positive bacteria. Here, we discovered a totally different activity of Bac: the neutralization of bacterial exotoxins. Bac prevented intoxication of mammalian cells with the binary enterotoxins Clostridium botulinum C2, C. perfringens ɩ, C. difficile transferase (CDT), and Bacillus anihracis lethal toxin. The transport (B) subunits of these toxins deliver their respective enzyme (A) subunits into cells. Following endocytosis, the B subunits f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 67 publications
1
10
0
Order By: Relevance
“…In a recent study, we already excluded that Bac inhibits endocytic mechanisms of cells [25]. In conclusion, Bac inhibits the pH-dependent membrane translocation of the catalytic subunit of TcdB, which is in accordance with the recent findings for other bacterial toxins that also deliver their catalytic subunit from acidic endosomes into the cytosol.…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…In a recent study, we already excluded that Bac inhibits endocytic mechanisms of cells [25]. In conclusion, Bac inhibits the pH-dependent membrane translocation of the catalytic subunit of TcdB, which is in accordance with the recent findings for other bacterial toxins that also deliver their catalytic subunit from acidic endosomes into the cytosol.…”
Section: Resultssupporting
confidence: 91%
“…In conclusion, a set of experiments was performed to demonstrate the toxin-neutralizing effects of Bac towards C. difficile TcdB in the human intestinal epithelial cells and stem-cell derived human intestinal organoids from this important C. difficile toxin, which is a major contributor to CDAD. In combination with the recent observation that Bac neutralizes the actin-modifying toxin CDT from hypervirulent C. difficile strains [25], the findings might offer a starting point for the development of novel therapeutic options in the context of CDAD, in particular because Bac is already an approved drug in clinical use [24]. The implementation of iPSC-derived intestinal organoids could further fortify a potential role for Bac in the direct treatment of C. difficile -induced toxicity.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…In addition to antibiotic properties, bacitracin was previously demonstrated to protect cultured human cells from intoxication by anthrax lethal toxin and CDT. 118 Zhu et al demonstrated that bacitracin protected Caco-2 and HIOs from TcdB activity, reducing downstream glucosylation of the target protein Rac1 and preventing depolymerization of F-actin in HIOs. 46 These experiments suggest that bacitracin, an approved drug for clinical use, has potential application to a combination therapy against C. difficile infection.…”
Section: Clostridium Difficilementioning
confidence: 99%